2007
DOI: 10.1128/iai.01632-06
|View full text |Cite
|
Sign up to set email alerts
|

Contributions of Histamine, Prostanoids, and Neurokinins to Edema Elicited by Edema Toxin fromBacillus anthracis

Abstract: Bacillus anthracis edema toxin (ET), composed of protective antigen and an adenylate cyclase edema factor (EF), elicits edema in host tissues, but the target cells and events leading from EF-mediated cyclic-AMP production to edema are unknown. We evaluated the direct effect of ET on several cell types in vitro and tested the possibility that mediators of vascular leakage, such as histamine, contribute to edema in rabbits given intradermal ET. ET increased the transendothelial electrical resistance of endotheli… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
46
2

Year Published

2007
2007
2017
2017

Publication Types

Select...
4
4
1

Relationship

0
9

Authors

Journals

citations
Cited by 34 publications
(49 citation statements)
references
References 66 publications
1
46
2
Order By: Relevance
“…This may reflect the exotoxins' ability to break down epithelial and endothelial cell barriers and cause hemorrhaging in animal models (22,57,74). The ability to affect endothelial barrier function can be seen even with low exotoxin concentrations (100 ng ET and 1 g LT) in vitro, where ET and LT alter the transendothelial electrical resistance of endothelial cell monolayers (69,74). Likewise, capsule plays an important role in dissemination.…”
Section: Dissemination Factorsmentioning
confidence: 99%
“…This may reflect the exotoxins' ability to break down epithelial and endothelial cell barriers and cause hemorrhaging in animal models (22,57,74). The ability to affect endothelial barrier function can be seen even with low exotoxin concentrations (100 ng ET and 1 g LT) in vitro, where ET and LT alter the transendothelial electrical resistance of endothelial cell monolayers (69,74). Likewise, capsule plays an important role in dissemination.…”
Section: Dissemination Factorsmentioning
confidence: 99%
“…This presumably would reduce diapedesis through capillaries or epithelial layers to the site of infection; however, this has not been tested [188]. These studies are in contrast to earlier work from Wade et al which found ET increases PMN chemotaxis and an in vivo observation that greater amounts of neutrophils were found near injection sites of ET [189,190].…”
Section: Immunological Effectscontrasting
confidence: 56%
“…Sec15/Rab11 are also inhibited by ET and LT in human brain microendothelial cell lines and suggested that ET induced edema indirectly by increasing inflammatory lipid mediators in vivo [189]. Furthermore, pharmacological inhibition of prostanoids, histamines, and neurokinins, which were postulated to induce histamine production, reduced edema formation via vascular leakage.…”
Section: Cardiovascular and Endothelial Effectsmentioning
confidence: 99%
“…This increase in vascular permeability does not appear to occur through a direct effect of edema toxin on endothelial cell function, however, but through the stimulation of multiple inflammatory mediators [18]. Inhibition of neurokinins, prostanoids and histamine reduce the vascular leakage caused by edema toxin, although the cell types that release these mediators have not been identified.…”
Section: Edema Toxinmentioning
confidence: 93%